Plano de projeto: serviço de geração de grades de horários de aula - Heisler , Daniel Afonso (Universidade do Vale do Rio dos Sinos, 2010)
For years, teachers, directors, course coordinators or academic secretaries from educational institutions, have suffered with the slow task of create sheets for class schedules. The difficulties range since the definition of what curricular component should occur in each learning period, go through the definition of what teachers can teach what curricular component and go until the question of available time of teachers. This paper is a project management plan to develop a system for the generation of sheets for class schedules that can be offered as an internet service.
Keywords: Plano de gerenciamento do projeto; Grades de horários de aula; Project management plan; Sheets of class schedules